A systematic review of sub-national food insecurity research in South Africa: Missed opportunities for policy insights. - Alison Misselhorn; Sheryl L Hendriks (PLoS ONE)
Food insecurity is an intractable problem in South Africa. The country has a tradition of evidence-based decision making, grounded in the findings of national surveys. However, the rich insights from sub-national surveys remain a largely untapped resource for understandings of the contextual experience of food insecurity. A web-based search identified 169 sub-national food insecurity studies conducted in the post-apartheid period between 1994 and 2014. The systematic review found that the studies used 27 different measures of food insecurity, confounding the comparative analysis of food insecurity at this level. While social grants have brought a measure of poverty relief at household level, unaffordable diets were the root cause of food insecurity. The increasing consumption of cheaper, more available and preferred 'globalised' foods with high energy content and low nutritional value lead to overweight and obesity alongside child stunting. Unless a comparable set of indicators is used in such surveys, they are not able to provide comparable information on the scope and scale of the problem. Policy makers should be engaging with researchers to learn from these studies, while researchers need to share this wealth of sub-national study findings with government to strengthen food security planning, monitoring, and evaluation at all levels.